PENYELENGARAAN PEMILIHAN WALI NAGARI SERENTAK DI KABUPATEN PADANG PARIAMAN TAHUN 2018 - Panala, Nazmi; Roza, Darmini; Sofiarti, Sofiarti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The implementation of village / Nagari head elections in the regions must be in accordance with the characteristics of the local community is in order to realize the implementation of village head elections that are honestly fair, beneficial, and to provide democratic political education to the community, which in turn increases public trust in their leaders , therefore the election of the Village Head must be continuously developed and adapted to the development of the community in the area or village. The Indonesian nation has expressly stated this in the (constitution) opening of the 1945 Constitution, the fourth paragraph which is the purpose of life of the nation and state, which is to protect the entire Indonesian nation and the entire bloodshed of Indonesia, and to promote public welfare, educate the nation's life. The democratic system in Indonesia, the community has the right, even the obligation to play politics to determine its future, play a role in making laws and regulations (law) and oversee its implementation. Laws in Indonesia are formed in the form of laws and regulations, so everyone who inhabits areas within the territory of the Republic of Indonesia must submit to him. Furthermore, from a political point of view, people do not only look at the implementation of an sich law, but also consider the consequences of a decision based on law on the interests of society, nation and state. Keywords: Election of Wali Nagari, Serentak, Padang Pariaman, 2018